The Effect of Using Digital Book to Ability Students’ Reading in Descriptive Text at Tenth Grade SMA Negeri 2 Rantau Selatan”. - Shopiah Anggraini Rambe; Anna Leli Harahap; Rizki Lestari; Gustiani Pratiwi; Muhammad Rusli; Nurhanna Harahap; Jupriaman (CV. AFDIFAL MAJU BERKAH, 2021)
Abstract This study aims to see whether there is an effect of using a digital book on the reading ability of students in class X SMA Negeri 2 Rantau Selatan. This study uses a quantitative approach with a quasi-experimental method. The population in this study were all class X-MIA SMA Negeri 2 Rantau Selatan and the sample was taken by 72 students with simple random sampling technique. The data technique used a written test in the form of an essay, the instruments used were pretest and posttest. Based on the t-test analysis using SPSS version 22 for windows, it is found that the value of t count< t table (1.241< 1.667). This shows that the ability to overcome students' reading skills by using digital books is better than students who use conventional learning models. Therefore, learning using a digital book can be used in implementing English learning at SMA Negeri 2 Rantau Selatan for the 2020/2021 school year.